Online Social Influencer: The Impact of Modern Marketing Toward M-Shopping - Yolanda Masnita, Pipie Puspitasari, Khomsiyah , Hermien (International Journal of Advanced Science and Technology, 2020)
Mobile platform resulted in smarter producers and consumers, ease of access for producers to market their products, and ease consumers in recognizing products. Mobile platform connects the people throughout the world. Mobile platform supported by technology give birth to online social network, which is a new transformational phenomenon, whereas individuals can share information, experience or connect with each other or within individual groups, thus an increase in the use of online social network is evident. This study focused on online social influencer who mediated subjective norm with the dimension of normative beliefs and motivation to comply which influenced consumers to perform purchases through mobile shopping. The approach of Theory of Planned Behavior (TPB) and Theory of Reasoned Action was used as the basis of analysis. A total of 347 participants in this study were consumers who at least had perform purchases through mobile shopping. Hypothesis was tested using LISREL. This study showed that online social influencer did not affect normative belief, neither directly nor indirectly. However, it affected motivation comply, both directly and as mediation.